Biochar-amended constructed wetlands for eutrophication control and microcystin (MC-LR) removal. (May 2022) - Cheng, Rui; Hou, Shengnan; Wang, Jingfu; Zhu, Hui; Shutes, Brian; Yan, Baixing
Abstract: Microcystins (MCs) pollution caused by eutrophication and climate change has posed a serious threat to ecosystems and human health. Constructed wetlands (CWs) with biochar addition volume ratios of 0% (BC0-CWs), 10% (BC10-CWs), 20% (BC20-CWs) and 50% (BC50-CWs) were set up to evaluate the efficiency of biochar-amended CWs for eutrophication and MCs pollution control. The results illustrated that removal efficiencies of both NH4 + -N and NO3 − -N were enhanced by biochar addition to varying degrees. The average TP and MC-LR removal efficiencies increased with increasing biochar addition ratios, and the average TP and MC-LR removal efficiencies in biochar-amended CWs were significantly ( p < 0.05) improved by 5.64–9.58% and 10.74–14.52%, respectively, compared to that of BC0-CWs. Biochar addition changed the microbial community diversity and structure of CWs. The relative abundance of functional microorganisms such as Burkholderiaceae, Nitrospiraceae, Micrococcaceae, Sphingomonadaceae and Xanthomonadaceae was promoted by biochar addition regardless of addition ratios. The higher relative abundance of the above microorganisms in BC20-CWs and BC50-CWs may contribute to their better removal performance compared to other CWs. The concentrations of extracellular polymeric substance (EPS) in biochar-amended CWs were significantly ( p < 0.05) lower than that in BC0-CWs, which can reduce the risk of system clogging. This study demonstrated that biochar addition may be a potential intensification strategy for eutrophication and MCs pollution control by CWs. Considering both the removal performance and economic cost, a biochar addition ratio of 20% was recommended as an optimal addition ratio in practical application. Graphical abstract: Image 1 Highlights: CWs with biochar addition ratios of 20% and 50% showed higher TP and MC-LR removal efficiency. Relative abundance of functional microorganisms was promoted by biochar addition. Content of extracellular polymeric substance was reduced in biochar-amended CWs.